Facilitating Human Research Ethics Review for Student Research : Final Report. - Wynn, Lisa L. (Office for Learning and Teaching, 2016)
Final report of a Teaching Fellowship at Macquarie University. This Fellowship explored the proposition that obtaining ethics clearance for research in disciplines that engage in human research is a significant barrier to developing a research-led curriculum. Interviews were conducted with 40 researchers and administrators from 14 Australian universities to find out what policies and procedures either hinder or facilitate a research-led undergraduate curriculum where students undertake empirical human research. Features of best practice and policy recommendations emerging from this research were communicated to study participants and to ethics administrators at Australian universities, sharing examples of what works and what doesn't.